MicroRNA-146a-5p Mediates High Glucose-Induced Endothelial Inflammation via Targeting Interleukin-1 Receptor-Associated Kinase 1 Expression - Lo, Wan-Yu; Peng, Ching-Tien; Wang, Huang-Joe (Frontiers in Physiology, 2017)
Background and aims: Interleukin-1 receptor-associated kinase-1 (IRAK-1) is critical for mediating toll-like receptor and interleukin-1 receptor signaling. In this study, we have examined whether IRAK-1 expression is altered in high glucose (HG)-stimulated human aortic endothelial cells (HAECs), and whether microRNAs (miRs) target IRAK-1 to regulate HG-induced endothelial inflammation. Methods: HAECs were treated with HG for 24 h and 48 h. Real-time PCR, Western blot, monocyte adhesion assay, bioinformatics analysis, TaqMan® arrays, microRNA mimic or inhibitor transfection, luciferase reporter assay and siRNA IRAK-1 transfection were performed. The aortic tissues from db/db type 2 diabetic mice were examined by immunohistochemistry staining. Results: HG time-dependently increased IRAK-1 mRNA and protein levels in HAECs, and was associated with increased VCAM-1/ICAM-1 gene expression and monocyte adhesion. Bioinformatic analysis, TaqMan® arrays, and real-time PCR were used to confirm that miR-146a-5p, miR-339-5p, and miR-874-3p were significantly downregulated in HG-stimulated HAECs, suggesting impaired feedback restraints on HG-induced endothelial inflammation via IRAK-1. However, only miR-146a-5p mimic transfection reduced the HG-induced upregulation of IRAK-1 expression, VCAM-1/ICAM-1 expression, and monocyte adhesion. Additionally, IRAK-1 depletion reduced HG-induced VCAM-1/ICAM-1 gene expression, and monocyte adhesion, indicating that HG-induced endothelial inflammation was mediated partially through IRAK-1. In vivo, intravenous injections of miR-146a-5p mimic prevented endothelial IRAK-1 and ICAM-1 expression in db/db mice. Conclusion: These results suggest that miR-146a-5p is involved in the regulation of HG-induced endothelial inflammation via modulation of IRAK-1; indicating that miR-146a-5p may be a novel target for the treatment of diabetic vascular complications.